2002
DOI: 10.1677/jme.0.0290125
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol up-regulates estrogen receptor messenger ribonucleic acid in endometrial carcinoma (Ishikawa) cells by stabilizing the message

Abstract: Estrogens up-regulate expression of the estrogen receptor alpha (ER) gene in most mammalian tissues studied. Using the ovariectomized ewe as a model, we determined that estradiol (E 2 ) acted post-transcriptionally to increase endometrial ER mRNA concentrations by enhancing the stability of the message. The purpose of this study was to determine whether a similar E 2 effect occurs in Ishikawa cells, a well-differentiated human endometrial adenocarcinoma cell line. The presence and function of ER protein in Ish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 52 publications
4
14
1
Order By: Relevance
“…In vivo, ovine uterine cells responded to estrogen treatment by up-regulating the transcription of ERa mRNA (Ing and Tornesi, 1997;Robertson et al, 2001). Estrogen also increased ERa mRNA levels in ZR-75 (Clayton et al, 1997) and Ishikawa cells (Robertson et al, 2002). However, estrogen treatment decreased ERa mRNA in ECC-1 (Farnell and Ing, 2003) and MCF-7 cells (Saceda et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo, ovine uterine cells responded to estrogen treatment by up-regulating the transcription of ERa mRNA (Ing and Tornesi, 1997;Robertson et al, 2001). Estrogen also increased ERa mRNA levels in ZR-75 (Clayton et al, 1997) and Ishikawa cells (Robertson et al, 2002). However, estrogen treatment decreased ERa mRNA in ECC-1 (Farnell and Ing, 2003) and MCF-7 cells (Saceda et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of estrogen to modulate ERα expression has been most extensively studied in cell lines (Treilleux et al, 1997;Robertson et al, 2002). One hypothesis suggests that estrogen induces trans-acting factors to bind to specific elements of ER mRNA molecules, and protects their ends.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a preferential expression of CREMα over the alternatively spliced isoform CREMtau2α is seen progressively within the myometrium from nonpregnant to pregnant and laboring stages, and this switch is mediated by the splicing factor SRp40 (24). β-Estradiol has also been shown to increase ER expression by stabilizing its mRNA (27). The estrogen-initiated suppression of IL-2 production ( Figure 5) may contribute to the pathogenesis of SLE, since it is clear that IL-2 is needed for the generation of cytotoxic responses, the generation of T regulatory cells and activationinduced cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the proliferative response of endometrial cells in culture to SERMs has been shown to be variable, largely due to conditional differences between dose, time of exposure or media components (Shah et al 2004). In this study, we used an established human uterine-derived epithelial cell line (Ishikawa; (Anzai et al 1989)), which is oestrogen-responsive (Holinka et al 1986, Robertson et al 2002 and shares many phenotypic features in common with normal human endometrial epithelial cells (Lessey et al 1996) to investigate the variation and extent of gene expression changes following tamoxifen treatment. Global gene expression profiles were determined and compared following treatment with 4-hydroxytamoxifen (OHT, 10 K6 M) or 17b-oestradiol (E 2 , 10 K8 M).…”
Section: Introductionmentioning
confidence: 99%